Quality analysis method of Web browsing based on big data - Weihua CHENG; Xiaorong HE (Dianxin kexue)
The traditional network operation and maintenance often focuses on the operation status of the network and equipment,which is difficult to solve the user's subjective perception.It is urgent to establish an end-to-end Internet application awareness management system.Focusing on the quality analysis of web browsing,the quality analysis framework and method of user perceived data based on big data technology was studied,a quality analysis system framework based on big data technology was designed and proposed,which was used to realize the quality analysis of Internet business.Taking an international website as an example,a diagnosis method of ＆quot;two looks and five cuts＆quot; was proposed to delimit and trace the cause,which improves the efficiency of manual analysis and verifies the effectiveness of the proposed method.